How Organizations Measure Success The Use of Performance Indicators in Government. (New York Routledge Florence Taylor & Francis Group [distributor], 1995)
Reports on two years of field research funded by the Economic and Social Research Council. Examines performance indicators across a variety of government departments and public agencies as well as private businesses.
Cover -- Title -- Copyrigght -- Contents -- List Of Tables -- List Of Abbreviations -- Introduction -- 1 Revolution Or Resurrection? The History Of A Concept -- 2 Models, Measures, And Muddles: Organisational And Conceptual Dimensions Of Performance I ndicators -- 3 The Criminal Justice System: Police, Courts, And Prisons -- 4 The Welfare System: Social Security And The National Health Service -- 5 The Private Sector: Banks, Building Societies, And Retail Stores -- 6 Managing Monopolies: Railways, Water, And Airports -- 7 Performance Indicators In The 1990S: Tools For Managing Political And Administrative Change -- References -- Name Index -- Subject Index.
Trade
Keywords: Administrative Agencies; Executive Departments -- Great Britain; Industrial Productivity; Electronic resource